Introduction to healthcare for Russian-speaking interpreters and translators - Crezee, Ineke; Hautekiet, Johanna; Rura, Lidia (John Benjamins Publishing Company, 2022)
"Health interpreters and translators often face unpredictable assignments in the multifaceted healthcare setting. This book is based on the very popular international publication (Crezee, 2013) and has been supplemented with commonly asked questions and glossaries in Russian. Just like the 2013 textbook, this practical resource will allow interpreters and translators to quickly read up on healthcare settings, familiarizing themselves with anatomy, physiology, medical terminology and frequently encountered medical conditions, diagnostic tests and treatment options. This is an exceptionally useful and easily accessible handbook, in particular for interpreters, translators, educators and other practitioners working between Russian and English. Russian-speakers represent a rich and diverse range of historical, religious and cultural traditions. This book covers some of those, while also describing the Russian health system, and touching on cultural beliefs and natural medicine approaches. This unique book is an indispensable vade mecum ('go with me') for anyone wanting to navigate language access involving speakers of Russian in the health setting"--